Let's talk politics : new essays on deliberative rhetoric - Belle, Hilde van (Argumentation in context, 2014)
The essay describes how Polish members of parliament (MPs) reinvented the institution of parliament (conceived of in its essentially discursive character as parleyment) in the course of the political transition of 1989. The reinvention of "parliamentary democracy" and deliberation in the chamber involved four interrelated developments: rearticulation of the "people" and thereby providing new basis for parliamentary "representation" and for the rhetorical agency of MPs; redefinition and rearticulation of the relationship between parliament and other organs of state power, especially government.